Counting the uncounted: The consequences of children's domestic chores for health and education in Ethiopia. Issue 3 (12th March 2019) - Dinku, Yonatan; Fielding, David; Genç, Murat
Abstract: Much of the existing literature on the economics of child labor assumes that child labor is synonymous with employment in income‐generating activities. However, children also perform domestic chores, and excessive involvement in chores may be detrimental to their wellbeing. This paper investigates the effect on child health and education outcomes of participation in domestic chores as well as participation in income‐generating activities. Our data come from the 2014 Young Lives survey of Ethiopia. We use the guidelines of the 18th International Conference of Labor Statisticians and the United Nations Children's Fund to make a distinction between light work and harmful work, and apply this distinction to both domestic chores and income‐generating work. Using an instrumental variables approach, we find that involvement in harmful domestic chores is strongly associated with poor health and education outcomes. Our findings suggest that excessive involvement in domestic chores constitutes a form of child labor. Ignoring domestic chores will lead to an underestimate of the prevalence of child labor, especially among girls, whose exposure to chores is much higher, on average, than that of boys.